2016
DOI: 10.1159/000454986
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Stress-Induced Analgesia: An Examination of Effects on Heat Pain Threshold and Tolerance and of Neuroendocrine Mediation

Abstract: Stress-induced analgesia (SIA) is an adaptive response of reduced nociception following demanding acute internal and external stressors. Although a psychobiological understanding of this phenomenon is of importance for stress-related psychiatric and pain conditions, comparably little is known about the psychobiological mechanisms of SIA in humans. The aim of this study was to investigate the effects of acute psychosocial stress on heat pain perception and its possible neuroendocrine mediation by salivary corti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…Considering the highly mixed results on the effect of acute stress on pain perception, it appears the type of stress and the magnitude of its appraisal determines its interaction with the pain system (Geva et al, 2014). Similarly, Gaab et al (2016) sought to explore the impact of acute psychosocial stress on heat pain perception in a healthy sample. Results showed that acute psychosocial stress did not impact heat pain threshold but did slightly increase heat pain tolerance, suggesting that psychosocial stress is selectively analgesic for heat pain tolerance.…”
Section: Acute Stress On Pain Perception and Sensory Functioning In Hmentioning
confidence: 99%
“…Considering the highly mixed results on the effect of acute stress on pain perception, it appears the type of stress and the magnitude of its appraisal determines its interaction with the pain system (Geva et al, 2014). Similarly, Gaab et al (2016) sought to explore the impact of acute psychosocial stress on heat pain perception in a healthy sample. Results showed that acute psychosocial stress did not impact heat pain threshold but did slightly increase heat pain tolerance, suggesting that psychosocial stress is selectively analgesic for heat pain tolerance.…”
Section: Acute Stress On Pain Perception and Sensory Functioning In Hmentioning
confidence: 99%
“…We defined posttreatment heat-pain tolerance as the primary outcome. Heat-pain tolerance is related to affective and motivational aspects ( 33 , 36 ) and implies experiencing maximum discomfort, which results in greater subjective stress ( 33 ). In addition, it has been associated with pathological pain, as there is an inverse relationship between ischemic pain tolerance and the perceived severity of clinical pain ( 37 ).…”
Section: Methodsmentioning
confidence: 99%
“…We assessed heat-pain tolerance and heat-pain threshold following the design of previous trials (33)(34)(35). We defined posttreatment heat-pain tolerance as the primary outcome.…”
Section: Measures Pain Ratingsmentioning
confidence: 99%
“…The stress-induced analgesia (SIA) is an adaptive antinociceptive response following exposure to internal and external stressors (Gaab et al , 2016). Stress and pain have a complex web of interactions and are considered a defensive response to actual or potential damage (Baker et al , 2019).…”
Section: Introductionmentioning
confidence: 99%